2004
DOI: 10.1002/jppr200434132
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Adverse Drug Reaction Reporting in New South Wales Teaching Hospitals

Abstract: Aim: To identify predisposing and enabling factors which influence adverse drug reaction reporting by medical, nursing and pharmacy staff in New South Wales teaching hospitals. Method: A questionnaire was distributed to all doctors, nurses and pharmacists in four New South Wales teaching hospitals. Health promotion concepts were used to provide a framework for interpreting results. Results: 4808 questionnaires were distributed and 1125 (23% response rate) were returned. Approximately 16% of respondents reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 11 publications
2
18
0
1
Order By: Relevance
“…These included is through training 106(49.5%). Several studies also agreed (24,29,(44)(45)(46), continuing education on pharmacovigillance 61(28.5%), incentives 15(7.0%) studies supported were (19,47). Apart from the fact that the use of incentives have not been widely accepted and practiced, it raises the possibility of overreporting by some health care workers in a bid to obtain financial rewards.…”
Section: Discussionmentioning
confidence: 76%
“…These included is through training 106(49.5%). Several studies also agreed (24,29,(44)(45)(46), continuing education on pharmacovigillance 61(28.5%), incentives 15(7.0%) studies supported were (19,47). Apart from the fact that the use of incentives have not been widely accepted and practiced, it raises the possibility of overreporting by some health care workers in a bid to obtain financial rewards.…”
Section: Discussionmentioning
confidence: 76%
“…However, some studies show statistically significant differences between the healthcare professionals. Among studies that included other healthcare professionals, pharmacists were more likely to see an ADE and more likely to be aware about the existence of pharmacovigilance centres and reporting forms compared to doctors and nurses . No difference in the mean knowledge/attitudes was found between the three healthcare professional in some studies or reporting rate .…”
Section: Resultsmentioning
confidence: 89%
“…Compared to pharmacy technicians, pharmacist found to have better knowledge of and attitudes towards ADE reporting . In a study conducted among HCPs in South Wales teaching hospitals, the majority of doctors and nurses indicated that the ward pharmacists are their main source of information about ADRs . However, a recent study from Ethiopia found that less than 7% of the surveyed HCPs used pharmacists as a source of information about ADRs …”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Knowing the factors that may confirm an adverse event will assist heath providers and physicians in establishing ways to correct underreporting. Different reasons that need to be analyzed in order to improve the quality of reporting [21]. There are huge numbers of reports that are available in the databases.…”
mentioning
confidence: 99%